An Analysis of Loan Loss Provisioning Behaviour in Chinese Banking Sector - CHENG, CHEN (2017)
The purpose of this dissertation is to examine the loan loss provisioning behaviour of Chinese banking system during the period of 2011 to 2016. This paper tests the capital management hypothesis, income smoothing hypothesis and business cycle hypothesis also analysis which financial factors have an impact on loan loss provision. The empirical results generated from this paper illustrate a significant negative relationship between capital management and loan loss provision (LLP), which is in line with most previous studies specified in China indicates Chinese bank managers have less incentive to manipulate the amount of LLP although using LLP to smooth income is a worldwide behaviour. Also, income smoothing is insignificant in relation to LLPs where a negative coefficient can be found, which suggests a negative relationship between discretionary LLP and Tier 1 capital before LLPs in Chinese banking system; moreover, business cycle shares a negative relationship with LLPs which is also insignificant, implies business cycle hypothesis has no obvious influence on the change of LLP in this model, mainly due to over interference from Chinese government. The instrument variables this paper used include return on average assets, however the result indicates ROAA is not a good financial variable when measuring banks profitability in China, this result also verify the study of Heffernan and Fu (2008), and suggested to utilize the net interest margin to substitute ROAA as an instrument variable.